Challenges in Implementing Authentic Assessment in English Language Courses at Higher Education Institutions - Monika Gultom (Jurnal Ragam Pengabdian, 2026)
The application of authentic assessment in English learning in higher education is increasingly considered important because it is able to assess students' communicative skills more clearly and relevant to the context of language use. However, the implementation of this assessment in the classroom still faces challenges that are often not seen in curriculum policies. This research aims to uncover and understand the main challenges faced in the implementation of authentic assessment in English courses in universities, with a focus on lecturers' pedagogical practices, institutional support, and student readiness. This research uses a qualitative approach with a case study design conducted at a university in Jayapura, Indonesia. Data were collected through semi- structured interviews with four English lecturers and eight students who were directly involved in performance-based assessments, then analyzed using thematic analysis. The results of the study show that the implementation of authentic assessment is constrained by the limited understanding of lecturers in designing clear and consistent assessment instruments, limited time and large class sizes, and low readiness of students in understanding assessment criteria. These findings show that there is a significant gap between competency-oriented learning demands and the real conditions of classroom assessment. The novelty of this research lies in the contextual disclosure of how these challenges interact with each other in the higher education environment in areas that are still rarely studied. This research emphasizes the importance of strengthening the role of institutions, increasing the capacity of lecturer assessments, and assessment transparency for students to improve the quality of authentic assessments in English learning in universities.